2022
DOI: 10.1038/s41598-022-15117-6
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of hybrid mediated blood flow in stenosis narrow arteries

Abstract: In this paper the behavior of flow of blood under stenosis suppositions is studied. Nanoparticles of Ag and Cu are being used with blood as base fluid. The problem governing equations are modeled into PDE’s, which are transformed into set of ODE’s with the help of useful similarity transformation. We investigated the solution numerically for various parameters on temperature and velocity distribution and shown in the form of tables and graphs. It is found that the velocity of blood increases while the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…More recent research employed mathematical modeling and gold nanoparticles to investigate their impact on blood flow and clotting risk in these arterial conditions [22,27]. Hussain et al [28] utilized mathematical modeling techniques and found that nanoparticles could enhance blood flow and reduce the risk of blood clots in narrow arteries affected by stenosis. However, it is important to acknowledge the potential risks associated with nanoparticle use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent research employed mathematical modeling and gold nanoparticles to investigate their impact on blood flow and clotting risk in these arterial conditions [22,27]. Hussain et al [28] utilized mathematical modeling techniques and found that nanoparticles could enhance blood flow and reduce the risk of blood clots in narrow arteries affected by stenosis. However, it is important to acknowledge the potential risks associated with nanoparticle use.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al. [28] utilized mathematical modeling techniques and found that nanoparticles could enhance blood flow and reduce the risk of blood clots in narrow arteries affected by stenosis. However, it is important to acknowledge the potential risks associated with nanoparticle use.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the effectiveness and efficiency of the heat transfer system, nanotechnology is introduced by suspending metallic and non-metallic nanoparticles in conventional fluids, which are known as nanofluids and were first introduced by Choi 22 . This enhancement method is important in many industries sector, such as biomedical, automotive, aerospace, petrochemical, and manufacturing 26 28 . The term "nanofluid" refers to a fluid adequately disseminated in conventional heat transfer fluids and contains solid nanoparticles or nanofibers with small volumetric amounts of nanometer-sized particles.…”
Section: Introductionmentioning
confidence: 99%
“…Research investigators keep their attention on blood flow through arteries with mule stenosis. The behavior of the flow of blood as a nanofluid through a stenosed artery was studied by Hussain et al [2]. They used similarity transformation for the solution of a differential equation.…”
Section: Introductionmentioning
confidence: 99%